Grain quality traits within the wheat (Triticum spp.) genepool: prospects for improved nutrition through de novo domestication - Zeibig, Frederike; Kilian, Benjamin; Özkan, Hakan; Pantha, Sumitra; Frei, Michael; Justus Liebig University Giessen (My University, 2024)
Background: Wild relatives of wheat (Triticum spp.) harbor beneficial alleles for potential improvement and de novo domestication of selected genotypes with advantageous traits. We analyzed the nutrient composition in wild diploid and tetraploid wheats and their domesticated diploid, tetraploid and hexaploid relatives under field conditions in Germany and compared them with modern Triticum aestivum and Triticum durum cultivars. Grain iron (Fe) and zinc (Zn) concentrations, phytate:mineral molar ratios, grain protein content (GPC) and antioxidant activity were analyzed across 125 genotypes. Results: Grain Fe and Zn concentrations in wild wheats were 72 mg kg−1 and 59 mg kg−1, respectively, with improved bioavailability indicated by Phytate:Fe and Phytate:Zn molar ratios (11.7 and 16.9, respectively) and GPC (231 g kg−1). By comparison, grain Fe and Zn concentrations in landrace taxa were 54 mg kg−1 and 55 mg kg−1, respectively, with lower Phytate:Fe and Phytate:Zn molar ratios (15.1 and 17.5, respectively) and GPC (178 g kg−1). Average grain Fe accumulation in Triticum araraticum was 73 mg kg−1, reaching 116 mg kg−1, with high Fe bioavailability (Phyt:Fe: 11.7; minimum: 7.2). Wild wheats, landraces and modern cultivars showed no differences in antioxidant activity. Triticum zhukovskyi stood out with high grain micronutrient concentrations and favorable molar ratios. It was also the only taxon with elevated antioxidant activity. Conclusion: Our results indicate alteration of grain quality during domestication. T. araraticum has promising genotypes with advantageous grain quality characteristics that could be selected for de novo domestication. Favorable nutritional traits in the GGAA wheat lineage (T. araraticum and T. zhukovskyi) hold promise for improving grain quality traits. © 2024 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.
Keywords: ddc:630